Analisis Peran Keluarga Terhadap Kreativitas Siswa - Siti Fuadah; Ahmad Suriansyah; Arta Mulya Budi Harsono; Yogi Prihandoko; Ari Hidayat (Journal Educational Research and Development | E-ISSN : 3063-9158, 2024)
The purpose of this study is to find out how the family plays a role in influencing student creativity. Creativity is critical to a child's intellectual and emotional development, and can also impact academic success and social adjustment. This research adopts a qualitative approach using a case study method involving various families with different socio-economic backgrounds. Data was collected through in-depth interviews with parents and teachers as well as observing student activities at home. The findings of this research indicate that support from the family is crucial in facilitating student creativity, including through providing emotional attention, providing educational resources, and creating an environment that supports the exploration of ideas. Apart from that, open education and providing opportunities to try new things have also been proven to contribute to the development of children's creativity. It is hoped that this research can provide understanding for parents, educators and other interested parties to pay more attention to the role of the family in encouraging the growth and development of students' creativity.